Management of foot degloving injury with bilateral anterolateral thigh flaps. (October 2020) - Zhou, Pan; Cong, Xiaobin; Chen, Zhenbing
Abstract: Foot degloving injuries are frequently encountered by reconstructive surgeons as there are more and more vehicles on the road. The separation between the deep facia and the superficial skin often damage the blood supply of the cutaneous tissue, resulting skin defect and digit necrosis. In order to manage these challenging situations, reconstructive surgeons have explored various types of techniques. Our team have managed to cure one such patient through bilateral anterolateral thigh flaps, in which the two flaps cover the dorsal and plantar side respectively. The flaps survived uneventfully and second stage operation of defatting was consequently arranged. The patient obtained protective sensation and felt satisfied with the cosmetic outcome. With the development of microsurgery, bilateral anterolateral thigh flaps could be effectively adopted to manage foot degloving injuries.